Elaboración de perfiles y el scoring crediticio: caracterización jurídica y aplicación del régimen legal peruano de protección de datos personales - Zegarra Valdivia, Diego; Gil Aguilar, Giovanna (Pontificia Universidad Católica del Perú, 2025)
The increasing use of automated mechanisms for the analysis of personal data, particularly profiling and credit scoring, poses significant challenges from a personal data protection perspective. Within the Peruvian legal system, the recent explicit incorporation of automated decision-making and profiling into the Regulation of the Personal Data Protection Law, approved by Supreme Decree 016-2024-JUS, requires a clear conceptual delimitation of these techniques, as well as an assessment of their compatibility with the principles and rights recognized under the current data protection framework.In this context, this article aims to characterize profiling and credit scoring, to determine their conceptual relationship, and to examine the conditions that must be ensured to guarantee the lawfulness of their implementation in the Peruvian financial sector. To this end, a doctrinal approach is adopted, based on the analysis of comparative law, specialized scholarship, and advisory opinions issued by the National Data Protection Authority.The paper argues that credit scoring constitutes a specific manifestation of profiling which, when integrated into decision-making processes producing legal effects, triggers the safeguards established under Article 87 of the Regulation of the Personal Data Protection Law. Consequently, its implementation requires a rigorous assessment of the applicable legal basis, the proper identification of the source of personal data, and a clear allocation of responsibilities between the data controller and the data processor.

El creciente uso de mecanismos de análisis automatizado de datos personales, particularmente la elaboración de perfiles (profiling) y el scoring crediticio, plantea importantes desafíos desde la perspectiva de la protección de datos personales. En el ordenamiento jurídico peruano, la reciente incorporación expresa de las decisiones automatizadas y de la elaboración de perfiles en el Reglamento de la Ley de Protección de Datos Personales, aprobado por Decreto Supremo 016-2024-JUS, exige una delimitación conceptual de estas técnicas, así como un análisis de su compatibilidad con los principios y derechos reconocidos por la normativa de protección de datos personales vigente.En ese sentido, el presente trabajo tiene como objetivo caracterizar la elaboración de perfiles y el scoring crediticio, determinar su relación conceptual y examinar las condiciones que se deben garantizar para la licitud de su implementación en el sector financiero peruano. Para ello, se adopta un enfoque dogmático, basado en el análisis del derecho comparado, la doctrina especializada y las opiniones consultivas de la Autoridad Nacional de Protección de Datos Personales.El texto pretende visibilizar que el scoring crediticio constituye una manifestación específica de la elaboración de perfiles que, cuando se integra a procesos de toma de decisiones con efectos jurídicos activa las garantías previstas en el artículo 87 del Reglamento de la LPDP. En consecuencia, su implementación exige una evaluación rigurosa de la base legal aplicable, la identificación adecuada de la fuente de los datos personales y la correcta delimitación de los roles del Responsable y del Encargado del tratamiento.
Profiling and credit scoring: legal characterization and application of the Peruvian legal regime for personal data protection
Keywords: Profiling; Credit Scoring; Automated Decision; Making; Personal Data Protection; Objective Processing; Peruvian Data; Protection Law; Financial Sector; Peru; Elaboración de Perfiles; Scoring Crediticio; Decisiones Automatizadas; Protección de Datos Personales; Tratamiento Objetivo; Reglamento de la LPDP; Sector Financiero; Perú; https://purl.org/pe-repo/ocde/ford#5.05.00